Abundance and Diversity of Arbuscular Mycorrhizal Fungi (AMF) in Soils under Different Rangeland Use Types in the Middle Awash Basin, Ethiopia - Terefe, Dawit; Belay, Zerihun; Assefa, Fasil; Kibret, Kibebew; Dechassa, Nigussie (East African Journal of Sciences, 2021)
Background: Shrinking of rangelands/natural grasslands has led to various inter-communal conflicts and loss of livelihoods among pastoralists in Ethiopia. Restoring the rangelands is an important step to be taken to alleviate the problem. Various aggressively spreading invasive weed species are threatening the existence and sustainability of rangelands/natural grasslands. In addition, moisture stress is a major hindrance to any efforts made to restore the rangeland/natural grasslands. The role of Arbuscular mycorrhizal fungi (AMF) in establishing plant seedlings and regenerating natural grasslands through enhancing water and nutrient uptake is well documented. Objective: The main objective of this study was to investigate the influence of land use and soil types on abundance and diversity of AMF in semi-arid rangeland areas of the Middle Awash Basin in the Ethiopian Rift Valley region. Materials and Methods: Representative rhizosphere soil samples were taken from different land use types (cultivated, open grassland, shrubland, and prosopis-invaded land) and used to assess AMF diversity and abundance in relation to soil physical and chemical characteristics. The same soil samples were used to establish trap cultures for spore formation and colonization assessment. Results: In the present study, morphological analysis from field soils and trap cultures revealed 16 distinct morphotypes belonging to 10 genera including Glomus (3), Claroideoglomus (3), Funneliformis (2), Rhizophagus (2) and one from each of Acaulospora, Entrophospora, Gigaspora, Sclerocystis, Scutellospora and Septoglomus. Spore abundance significantly varied, ranging from 265–481 and 319–488 (100-g-1) in trap culture and field soil samples, respectively. Grassland soil samples displayed the highest spore abundance, followed by soil samples from shrubland and cultivated fields, with the lowest records from prosopis-invaded land use type. However, sporulation and level of colonization were higher in cultivated lands, which have lower spore abundance than open grass and shrublands. Conclusion: The results of the study indicated that converting land use from traditionally managed rangelands/grazing system to cultivated lands leads to encroachment by Prosopis spp. on the lands and significantly reduces AMF spore abundance, diversity, and percentage root colonization. Thus, the ever-expanding encroachment of prosopis on the open grasslands and croplands around the Awash River necessitates implementing strict measures to decrease pressure on the soil biota underneath.